Molecular phylogeny supports the paraphyletic nature of the genus Trogoderma (Coleoptera: Dermestidae) collected in the Australasian ecozone. - Castalanelli, Mark; Baker, A.; Munyard, Kylie; Grimm, M.; Groth, David (Cambridge University Press 2010, 2012)
To date, a molecular phylogenetic approach has not been used to investigate the evolutionary structure of Trogoderma and closely related genera. Using two mitochondrial genes, Cytochrome Oxidase I and Cytochrome B, and the nuclear gene, 18S, the reported polyphyletic positioning of Trogoderma was examined. Paraphyly in Trogoderma was observed, with one Australian Trogoderma species reconciled as sister to all Dermestidae and the Anthrenocerus genus deeply nested within the Australian Trogoderma clade. In addition, time to most recent common ancestor for a number of Dermestidae was calculated. Based on these estimations, the Dermestidae origin exceeded 175 million years, placing the origins of this family in Pangaea.